2015
DOI: 10.1007/s12646-014-0285-3
|View full text |Cite
|
Sign up to set email alerts
|

The Social Representations of Academic Achievement and Failure

Abstract: This study tried to explore the ways in which the construct of academic achievement and failure is conceptualized and represented among different social categories based on educational roles. It was indicated that social representations of academic achievement and failure function in broader social contexts. Findings also suggested that academic achievement and failure are not the antinomies and have multidimensional aspects which collaborate and have greater bearing on the future social outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Consent was obtained from 107 students' (Age range between 13 to 14 yrs), 30 parents (Age range between 34 to 40 yrs) and 15 teachers (Age range between 30 to 40 yrs). Responses from five students who withdraw latter from the study and two students who were not able to give response both verbally and in writing were not taken into account (see Sinha & Mishra, 2015) 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consent was obtained from 107 students' (Age range between 13 to 14 yrs), 30 parents (Age range between 34 to 40 yrs) and 15 teachers (Age range between 30 to 40 yrs). Responses from five students who withdraw latter from the study and two students who were not able to give response both verbally and in writing were not taken into account (see Sinha & Mishra, 2015) 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Email: csinha@jgu.edu.in, sinchetan@gmail.com discourses or go beyond. In the recent research on the similar lines, the meaning of academic achievement and failure were explored and it was observed that they are not antinomies but socially represented in multidimensional ways (Sinha & Mishra, 2015). Further, researches in different social science disciplines affirmed the predictive effect of family and school in the students' academic achievement and failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in the colonial countries, esample, India, the essence of colonial mindset in the name of modernity is still reflected in the form of competition, ability, achievement, aspirations and meritocracy discourses (see Kumar, 2009;Majumdar & Mooij, 2012;Sinha, 2013). In an Indian educational context, these discourses were found to have elements of individual and cognitive factors which were socially represented among students, parents and teachers (see Sinha & Mishra, 2015). The other notions of academic achievement and failure, however, were found to have less importance among those communities.…”
Section: One Of the Essential Tasks Of Progressive Educational Praxismentioning
confidence: 99%
“…SSS/394). The location of the research conducted and the structure of the topic was later amended with approval.2 This study was conducted on the same sample along with the study to understand the social representations of academic achievement and failure published somewhere else(Sinha & Mishra, 2015)…”
mentioning
confidence: 99%